"Peering through the window looking in": postgraduate experiences of non-belonging and belonging in relation to mental health and wellbeing. (11th April 2021) - Morris, Charlotte
Abstract : Purpose: The purpose of this paper is to explore belonging in relation to postgraduate wellbeing in the light of renewed concerns about the mental health and wellbeing this group of learners. It attends to postgraduates' subjective wellbeing, identifying ways in which this is intertwined with a sense of belonging. Belonging is situated in relation to the social domains of postgraduate experiences. This paper seeks to contribute in-depth understandings of postgraduate experiences, to make recommendations for practice and to identify fruitful paths for further theorisation and research. Design/methodology/approach: Two qualitative data sets situated in UK higher education are drawn on here: firstly, longitudinal qualitative data entailing 33 narrative interviews and written reflections of doctoral researchers were collected as part of a phenomenological study of doctoral learning. Secondly, interview data from 20 postgraduates (including masters, professional doctorates and PhD researchers) were collected as part of mixed method qualitative case study research into postgraduate wellbeing. Postgraduate participants were based in the social sciences, humanities, arts and professional disciplines at a cross-section of UK higher education institutions. Data were analysed thematically with a focus on interconnections between wellbeing, learning and belonging. Findings: A sense of belonging arose as a key contributing factor to postgraduate wellbeing. Belonging emerged as multi-faceted, interlinking with spatial, relational and cultural factors which are likely to be experienced in different ways and degrees depending on positionalities. Experiences of belonging and non-belonging are understood as produced through academic cultures and structural inequities. They also pertain to the uncertain, in-between position of postgraduate learners. For postgraduates, and doctoral researchers especially, reaching a sense of belonging to academia was a profoundly important aspect of their journeys. Conversely, lack of belonging is linked with poor mental wellbeing and engagement with studies. Originality/value: This paper engages with the neglected social domain of wellbeing. Attending to subjective perceptions of wellbeing enabled nuanced understandings of the links between wellbeing and belonging. It identifies spatial, relational and cultural dimensions of postgraduate belonging, contributing an understanding of how feelings of non-belonging manifest, how belonging might be nurtured, and how this potentially contributes to postgraduates' wellbeing.